Concentrated Solar Thermal Energy Technologies Recent Trends and Applications (Springer Proceedings in Energy,, 2018)
The proceedings entitled "Concentrated Solar Thermal Technologies: Recent Trends and Applications" includes the peer-reviewed selected papers those are presented during NCSTET 2016. The sub-topics under concentrated solar thermal technologies and applications included in the book are Solar Field; Receiver and Heat Exchanger; Coating; Thermal Energy Storage; Cooling; Process Heat; and Smart Grid and Policy Research. The domains mentioned cover topics from resource-assessment, collection to conversion of solar energy for applications, like, heating, cooling and electricity. The proceedings also include invited lectures from domain experts. The edited work will be useful for beginners and for the advanced level researchers in the field of concentrated solar thermal technologies and their applications.